Multifunctional Pacemaker Lead for Cardiac Energy Harvesting and Pressure Sensing. Issue 11 (28th April 2020) - Dong, Lin; Closson, Andrew B.; Jin, Congran; Nie, Yuan; Cabe, Andrew; Escobedo, Danny; Huang, Shicheng; Trase, Ian; Xu, Zhe; Chen, Zi; Feldman, Marc D.; Zhang, John X. J.
Abstract: Biomedical self‐sustainable energy generation represents a new frontier of power solution for implantable biomedical devices (IMDs), such as cardiac pacemakers. However, almost all reported cardiac energy harvesting designs have not yet reached the stage of clinical translation. A major bottleneck has been the need of additional surgeries for the placements of these devices. Here, integrated piezoelectric‐based energy harvesting and sensing designs are reported, which can be seamlessly incorporated into existing IMDs for ease of clinical translation. In vitro experiments validate the energy harvesting process by simulating the bending and twisting motion during heart cycle. Clinical translation is demonstrated in four porcine hearts in vivo under various conditions. Energy harvesting strategy utilizes pacemaker leads as a means of reducing the reliance on batteries and demonstrates the charging ability for extending the lifetime of a pacemaker battery by 20%, which provides a promising self‐sustainable energy solution for IMDs. The additional self‐powered blood pressure sensing is discussed, and the reported results demonstrate the potential in alerting arrhythmias by monitoring the right ventricular pressure variations. This combined cardiac energy harvesting and blood pressure sensing strategy provides a multifunctional, transformative while practical power and diagnosis solution for cardiac pacemakers and next generation of IMDs. Abstract : Self‐sustainable energy generation represents a new frontier of power solution for implantable biomedical devices (IMDs). An integrated cardiac energy harvesting and pressure sensing strategy is developed by using the porous P(VDF‐TrFE) films with a self‐assembly helical structure. It provides a multifunctional, transformative while practical power and diagnosis solution for cardiac pacemakers and the next generation of IMDs.